Conventional and unconventional participation in Latin America: a hierarchical latent class approach. Issue 4 (28th October 2021) - Alvarez, R. Michael; Katz, Gabriel; Levin, Ines; Núñez, Lucas
Abstract: Building on past research, we implement a hierarchical latent class model to analyze political participation from a comparative perspective. Our methodology allows simultaneously: (i) estimating citizens' propensity to engage in conventional and unconventional modes of participation; (ii) classifying individuals into underlying "types" capturing within- and cross-country variations in participation; and (iii) assessing how this classification varies with micro- and macro-level factors. We apply our model to Latin American survey data. We show that our method outperforms alternative approaches used to study participation and derive typologies of political engagement. Substantively, we find that the distribution of participatory types is similar throughout the continent, and that it correlates strongly with respondents' socio-demographic characteristics and crime victimization.